The Gift : 12 Lessons to Save Your Life - Eger, Edith Eva (2020)
This practical and inspirational guide to healing from the bestselling author of 'The Choice' shows how to release your self-limiting beliefs and embrace your potential. The prison is in your mind. The key is in your pocket. In the end, it's not what happens to us that matters most - it's what we choose to do with it. We all face suffering - sadness, loss, despair, fear, anxiety, failure. But we also have a choice; to give in and give up in the face of trauma or difficulties, or to live every moment as a gift. Celebrated therapist and Holocaust survivor, Dr Edith Eger, provides a hands-on guide that gently encourages us to change the imprisoning thoughts and destructive behaviours that may be holding us back.
Keywords: Resilience (Personality trait); Life change events -- Psychological aspects; Self-actualization (Psychology); Psychology